The (Un)Finished Ukrainian World War II - Lysenko, Oleksandr (Genocidas ir rezistencija, 2023)
The text examines one of the most difficult periods in the history of people of Ukraine – the events of the World War II. The purpose of this survey is to show the existential nature of the largest armed conflict in the history of mankind for Ukrainians, which was determined by the real threat of depopulation, as well as the deprivation of their natural right to self-determination. Not only great and influential, but also smaller actors of international arena had their own interests in Ukrainian territories, raw materials, and industrial and human resources. However, Moscow considered Ukraine to be the sphere of its undivided domination and used all means to solve the “Ukrainian question” according to its own scenarios. The first Sovietisation unequivocally confirmed the Kremlin’s intentions to implement the Bolshevik project in the Ukrainian regions annexed in 1939–1940. Under the collision of two totalitarian systems – Soviet and Nazi – Ukrainian political independence-oriented forces managed to organise themselves for resistance and protection of the indigenous interests of the people of Ukraine. The organisation of Ukrainian nationalists, as well as representatives of other political groups created their own armed formations – such as “Poliska Sich”, the Ukrainian Insurgent Army, self-defence units – which launched a struggle against the German and Soviet occupational forces and administration. This asymmetric confrontation had great political and moral-psychological significance, affirming the vitality of the “Ukrainian idea” and the continuity of the struggle for the restoration of Ukrainian statehood. The Stalinist regime needed more than 10 years to suppress the national liberation movement in Ukraine. Yet Ukrainians did not come to terms with communist tyranny and resisted it until the fall of the Soviet Union. In the current confrontation with the Russian aggression, Ukraine is finally breaking with its imperial past and establishing it as an independent, democratic state.